MASTERING ARTICLES: A BEGINNER'S GUIDE TO NAVIGATING ENGLISH GRAMMAR - M.S.Maxsudova; N.I.Mahsudova (PEDAGOGS, 2024)
Abstract: Are you a beginner English learner struggling with when to use "a," "an," or "the"? Mastering articles is an essential step in understanding English grammar, and it's a common hurdle many language learners face. In this article, we'll explore the basics of articles and provide practical tips for beginner students to improve their usage.